Research on Transient Characteristic of Stress Field of Friction Pair During Soft Start-up Process of Hydro-viscous Drive - Qiliang Wang; Hongwei Cui; Zisheng Lian; Long Li (Jixie chuandong)
In order to investigation the distribution characteristic of stress field of friction pairs in hydro-viscous drive during soft start-up process， Abaqus software is used to establish a three-dimensional thermal elastic analysis model of friction pairs. The indirect coupling numerical analysis method is adopted to predict the transient characteristics of stress field. In addition， the sensitivity of parameters is analyzed. The research results show that the thermal stress of the steel disc increases gradually during soft start-up process and reaches the maximum value at the end of the start-up process. And the position of the maximum value gradually approaches the central area. The oil grooves provide a good cooling effect and the maximum thermal stress of the friction lining appears at the edge of each rhombic region. The elastic modulus and thermal expansion positively impact the stress. Conversely， the thickness and Poisson's ratio negatively impact the stress. But the variance of parameters has no effect on the location of the maximum thermal stress. The analysis results provide reference for selecting the structural and material parameters of friction pairs.